Getting to Know My Superego: A Student Psychotherapist’s Heuristic Self-Search Inquiry Into Her Superego - Hoon, Teressa Poh Suan (Auckland University of Technology, 2022)
The superego is conceptualised by Freud (1923/1961c, 1933/1964) as the psychic agency that is responsible for the functions of conscience, ego ideal, and self-observation. Superego is viewed as an important dimension within a psychotherapist’s interiority that influences their personal and professional development. A personal struggle, combined with an unforgettable event in my clinical training, evoked a passionate concern in me to examine my experience of my superego as a student psychotherapist. A heuristic self-search inquiry was chosen as the methodology of this study due to its flexibility, accommodation of the researcher’s essence, and potential outcome of personal transformation. The focus of my inquiry is the qualitative aspects of my experience and their attached personal meanings. As I elucidated my experience of my superego, I discovered its harshness which revolves around a theme of safety. As I deepened my understanding of my superego, from the point of personal meanings, I experienced changes in myself. I discuss the implications of my personal findings on my learning and development as a student psychotherapist and my understanding of the superego concept.